Risk Analysis of Post-Disaster Logistics Distribution Failure - Herdianti, Wenny; Adji, Bayu Martandto; Ophiyandri, Taufika (Universitas Negeri Padang, 2024)
In conducting logistical activities of disaster relief in natural disaster management. it is often not possible to implement as it should. and there are always potential risks that arise. One of the problems faced is the delayed distribution of post-disaster logistics. Therefore. risk management is necessary so that disaster relief logistics activities can run well. In addition. there is a need for a risk mitigation strategy to mitigate potential risks in the post-disaster logistics distribution process. The study aims to identify potential risks to post-disaster logistics distribution activities and find out which risk management strategies are a priority to address immediately. Failure Mode and Effect Analysis (FMEA) is a systematic approach to identifying failures and giving a value or score to each risk. From the results of the study. 32 potential risks occurred. As a result. 13 risks were identified with RPN values above critical point values. Thus. 13 were obtained as priority management risks. where the risks with the top 3 RNA values are Disruption of the post-earthquake telephone network Difficulty coordination of the logistics team with a rating of 25.98. Long logistic delivery travel time with a value of 21.86. and Condition of the vehicle used is not good with a score of 21.66. Thus. for 13 of these risks. mitigation is carried out for treatment priorities. Risk management strategies are applied to risks that have RPN values above critical values to minimize the impact.